UiO-66-NH2-F4-coated ANF fiber aerogel as well as preparation method and application thereof

By evenly loading UIO-66-NH2-F4 on the surface of the ANF fiber and forming a three-dimensional multi-level hole structure, the fiber gas gel has solved the lack of performance of the existing MOF materials in CO2 capture, and achieved efficient CO2 adsorption and harmony Excellent mechanical performance.

CN119327431AActive Publication Date: 2025-01-21QINGDAO UNIV

Patent Information

Application Number
CN202411493159.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the CO2 capture, existing MOF materials have problems such as uneven mesoporous distribution, poor mechanical properties, poor moisture resistance and low CO2 adsorption capacity.

Method used

Use UIO-66-NH2-F4@ANF fiber gas gel, prepare aramic nano-fiber through high-voltage homogeneous legal system, and promote UIO-66-NH2-F4 on the ANF surface through phosphate treatment Technology has a gas gel with a three -dimensional multi -level hole structure.

Benefits of technology

It significantly improves the adsorption capacity of CO2, improves the compression and stability of the compression of gas gel, and improves the efficient diffusion and adsorption efficiency of CO2 gas molecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327431A_ABST
    Figure CN119327431A_ABST
Patent Text Reader

Abstract

The invention discloses UiO-66-NH2-F4 (at) ANF fiber aerogel and a preparation method and application thereof.The UiO-66-NH2-F4 (at) ANF fiber aerogel comprises an MOF precursor and an aramid nanofiber ANF, the MOF precursor comprises zircon salt, 2-aminoterephthalic acid H2BDC-NH2 and 2, 3, 5, 6-tetrafluoroterephthalic acid H2BDC-F4, and the aramid nanofiber ANF is prepared from an aramid nanofiber ANF, an aramid nanofiber ANF and a zirconium salt. The mass ratio of the zirconium salt to the H2BDC-NH2 to the H2BDC-F4 to the ANF is (0.8 to 1.2) to (1 to 1.5) to (1 to 1.5) to (0.8 to 1.2); the specific surface area of the UiO-66-NH2-F4-coated ANF fiber aerogel is 728.52 m < 2 > / g, the pore volume is 0.628 cm < 3 > / g, and the average pore size is 0.519 nm. The UiO-66-NH2-F4-coated ANF fiber aerogel has the advantages that a large amount of MOF can be uniformly loaded on the surface of the ANF fiber, the UiO-66-NH2-F4-coated ANF fiber aerogel has excellent compression resilience, a three-dimensional hierarchical pore structure and excellent wet stability, and the CO2 adsorption capacity can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fiber aerogels, and in particular relates to a UiO-66-NH2-F4@ANF fiber aerogel and a preparation method and application thereof. Background Art

[0002] Faced with the continued growth of global greenhouse gas emissions and the intensification of climate warming, in-depth and extensive research has been carried out on CO2 capture technology at home and abroad. Metal organic frameworks (MOFs) have been widely reported and applied to CO2 capture due to their excellent structural characteristics such as high specific surface area, high porosity, adjustable pore size, and easy surface functionalization. However, in order for MOFs to truly approach or meet the demand for high-performance CO2 adsorbents in the industrial field, the following problems still need to be solved: (1) How to accelerate the gas mass transfer performance of MOF and expand its pore structure and compression elasticity to achieve efficient fluidity and mass transfer efficiency of CO2 gas molecules inside it; (2) How to regulate the physical and chemical microenvironment of MOF to enhance its affinity for CO2, thereby achieving high CO2 adsorption capacity and high CO2 adsorption selectivity; (3) How to improve the chemical stability of MOF to expand its application possibilities in high humidity environments.

[0003] Therefore, there is an urgent need to develop a new MOF material to solve the defects of existing MOF materials such as uneven mesopore distribution, poor mechanical properties, poor moisture resistance, and low CO2 adsorption capacity. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a UiO-66-NH2-F4@ANF fiber aerogel and a preparation method and application thereof. The present invention can load MOF uniformly and in large quantities on the surface of ANF fibers. The UiO-66-NH2-F4@ANF fiber aerogel of the present invention has excellent compression resilience, a three-dimensional multi-level pore structure and excellent wet stability, and can effectively improve the CO2 adsorption capacity.

[0005] To this end, the present invention provides a UiO-66-NH2-F4@ANF fiber aerogel, comprising: a MOF precursor and an aramid nanofiber ANF, wherein the MOF precursor comprises a zirconium salt, 2-aminoterephthalic acid H2BDC-NH2 and 2,3,5,6-tetrafluoroterephthalic acid H2BDC-F4; the mass ratio of the zirconium salt, H2BDC-NH2, H2BDC-F4 and ANF is (0.8-1.2): (1-1.5): (1-1.5): (0.8-1.2); the specific surface area of ​​the UiO-66-NH2-F4@ANF fiber aerogel is 600-750 m 2 / g, pore volume is 0.5-0.8cm3 / g, and the average pore size is 0.3-1nm.

[0006] The present invention also provides a method for preparing the UiO-66-NH2-F4@ANF fiber aerogel, comprising: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Cut the aramid fibrils into pieces, add them into an alkaline solution, reflux them in a constant temperature water bath, and after the solution is cooled, filter and wash the solution with distilled water until it is neutral to obtain an aramid fibril solution; (1.2) High-pressure homogenization treatment: using a high-pressure homogenizer to treat the aramid fibril solution to obtain an aramid nanofiber solution; filtering the aramid nanofiber solution to remove water to obtain aramid nanofibers; (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: adding the aramid nanofibers to the PA solution and stirring under water bath conditions; then washing the ANF with distilled water until it is neutral and preparing an ANF aqueous dispersion; (3) Preparation of UiO-66-NH2-F4 fiber aerogel (3.1) Place the ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare an ANF / DMF dispersion; (3.2) Weighing a zirconium salt, adding it to the ANF / DMF dispersion, and stirring until it is completely dissolved; then adding H2BDC-NH2, H2BDC-F4 and glacial acetic acid HOAc, and continuing to stir to obtain a mixed solution; (3.3) transferring the mixed solution to a reactor for reaction, and after the reaction is completed and cooled to room temperature, obtaining UiO-66-NH2-F4@ANF fibers by suction filtration; (3.4) Wash the UiO-66-NH2-F4@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-66-NH2-F4@ANF fiber dispersion; (3.5) Take the UiO-66-NH2-F4@ANF fiber dispersion, add aqueous silane solution and tert-butyl alcohol, stir, and obtain UiO-66-NH2-F4@ANF fiber aerogel through freeze drying and thermal curing.

[0007] Preferably, in step (1.1), the alkaline solution is a sodium hydroxide solution with a concentration of 10-20 wt %; the ratio of the mass of the aramid fibers to the volume of the alkaline solution is (1-3) g: (300-800) ml; Reflux in a constant temperature water bath at 70-90℃ for 3-5h.

[0008] Preferably, in the step (1.2), the concentration of the aramid nanofiber solution is 0.3-0.6 wt%; the process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to increase the pressure to 700-900 MPa and treating for 15-25 min; then using a flat valve to increase the pressure to 900-1100 MPa and treating for 20-40 min.

[0009] Preferably, in step (2), the concentration of the PA solution is 15-25wt.%; the ratio of the mass of the aramid nanofiber to the volume of the PA solution is (0.5-1.5) g: (200-400) ml; stirring is performed for 2 h in a 40°C water bath; and the concentration of the ANF aqueous dispersion is 0.2-0.5wt%.

[0010] Preferably, in the step (3.1), the concentration of the ANF / DMF dispersion is 0.2-0.5 wt %.

[0011] Preferably, in the step (3.2), the mass ratio of the glacial acetic acid to the zirconium salt is (0.8-1.2):(3-6).

[0012] Preferably, in the step (3.3), the reaction temperature in the reactor is 110-130° C. and the reaction time is 10-14 h; and in the step (3.4), the concentration of the UiO-66-NH2-F4@ANF fiber dispersion is 0.2-0.5 wt %.

[0013] Preferably, in the step (3.5), the volume of the UiO-66-NH2-F4@ANF fiber dispersion, the mass of the aqueous silane solution and the volume ratio of the tert-butanol are (8-12) mL: (0.01-0.05) g: (0.5-1.5) ml; the freeze-drying temperature is -60--40°C, and the time is 30-40 h; the thermal curing temperature is 160-200°C, and the time is 3-8 min.

[0014] The present invention also provides the use of the UiO-66-NH2-F4@ANF fiber aerogel in the preparation of carbon dioxide separation and / or adsorption materials.

[0015] Compared with the prior art, the advantages and positive effects of the present invention include: (1) Compared with the traditional method of using potassium hydroxide (KOH) and 2-methyl sulfoxide (DMSO) to first deprotonate the aramid primary fiber and then use water as a proton donor to reduce it to obtain ANF, the present application adopts a high-pressure homogenization process to convert micron-sized aramid fibers into aramid nanofibers ANF, which can realize the batch preparation of ANF without the use of organic solvents. The ANF production efficiency is high and it is safe, environmentally friendly and pollution-free.

[0016] (2) Phosphoric acid treatment of ANF can expose a large number of active groups (such as amino and carboxyl groups) on the surface of ANF, thereby allowing ANF to react with metal Zr 4+ A strong interfacial hydrogen bond is formed between them, and finally UiO-66-NH2-F4 is uniformly and heavily loaded on the ANF surface, which can better promote the in situ growth of UiO-66-NH2-F4 on the ANF surface.

[0017] (3) MOF fiber aerogel can be reconstructed in three dimensions through fiber freeze-drying technology. Aqueous silane is added to the aqueous dispersion of UiO-66-NH2-F4 fibers, and block-shaped UiO-66-NH2-F4 fiber aerogel is obtained after freeze-drying. The block-shaped UiO-66-NH2-F4 fiber aerogel is then subjected to high-temperature thermal curing treatment to obtain UiO-66-NH2-F4 fiber aerogel with enhanced mechanical properties. The aerogel exhibits excellent compression-rebound properties and can maintain a complete aerogel morphology after 800 compression-rebound tests.

[0018] (4) The UiO-66-NH2-F4 fiber aerogel of the present invention has a three-dimensional multi-level pore structure integrating macropores, mesopores and micropores, wherein the macropores and mesopores formed by the three-dimensional interconnected fiber network can be used as continuous long-range gas transmission channels, effectively improving the efficient diffusion of gas molecules inside it; and the UiO-66-NH2-F4 distributed in the three-dimensional nanofiber network channel retains an open microporous structure, which can provide more contact area, active sites and transmission channels for CO2, thereby improving its adsorption capacity for CO2; at the same time, the hydrophobic micropores can also limit H2O molecules and promote the adsorption of CO2 molecules into the interior of the UiO-66-NH2-F4 fiber aerogel.

[0019] (5) The MOF precursor of the present application includes zirconium chloride (ZrCl4) and two organic ligands, 2-aminoterephthalic acid (H2BDC-NH2) and 2,3,5,6-tetrafluoroterephthalic acid (H2BDC-F4). The fluorination modification design using the ligand H2BDC-F4 containing non-polar functional groups such as fluorine can greatly improve the wet stability of the MOF chemical microenvironment, expand its application possibilities in high humidity environments, and transform the MOF from hydrophilic to hydrophobic, thereby constructing a microporous environment that is hydrophilic to CO2 molecules and hydrophobic to H2O molecules. When using ligands with polar functional groups (such as amino and carboxyl groups), the microporous environment of MOF can have a strong affinity for CO2 molecules.

[0020] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM image of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1; Figure 2 The stress-strain curve of the UiO-66-NH2-F4@ANF fiber aerogel in Example 1 was measured by a compression-rebound test with 800 cycles under the test condition of 50% deformation; Figure 3 This is a pore size distribution test diagram of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1; Figure 4 This is the SEM image of the ANF fiber aerogel of Comparative Example 1; Figure 5 This is a test graph of CO2 adsorption capacity of UiO-66-NH2-F4@ANF fiber aerogel of Example 1 and ANF fiber aerogel of Comparative Example 1 at 25°C; Figure 6 This is a test graph of the adsorption capacity of H2O (gaseous state) of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 and the ANF fiber aerogel of Comparative Example 1 at 25°C; Figure 7 These are the XRD test patterns of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1, the ANF fiber aerogel of Comparative Example 1, and the UiO-66-NH2-F4 crystal. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0023] The UiO-66-NH2-F4@ANF fiber aerogel of the invention comprises a MOF precursor and aramid nanofiber ANF, wherein the MOF precursor comprises a zirconium salt, 2-aminoterephthalic acid H2BDC-NH2 and 2,3,5,6-tetrafluoroterephthalic acid H2BDC-F4.

[0024] The mass ratio of zirconium salt, H2BDC-NH2, H2BDC-F4 and ANF is (0.8-1.2): (1-1.5): (1-1.5): (0.8-1.2). Within the above mass ratio range, UiO-66-NH2-F4 particles (i.e., MOF precursor) of suitable particle size can be obtained, which effectively avoids the stacking distribution of UiO-66-NH2-F4 particles on the surface of ANF, so that UiO-66-NH2-F4 particles can be uniformly loaded on the surface of ANF, effectively improving the specific surface area of ​​UiO-66-NH2-F4@ANF fiber aerogel, which is conducive to obtaining aerogel with a three-dimensional porous structure and CO2 gas transfer, thereby improving the adsorption capacity of aerogel for CO2.

[0025] The UiO-66-NH2-F4@ANF fiber aerogel of the present invention has excellent thermal insulation performance, and the thermal conductivity at 25°C can be as low as 27 mW / mk.

[0026] The specific surface area of ​​the UiO-66-NH2-F4@ANF fiber aerogel of the present invention is 600-750m 2 / g, pore volume is 0.5-0.8cm 3 / g, and the average pore size is 0.3-1nm.

[0027] Preferably, the specific surface area of ​​the UiO-66-NH2-F4@ANF fiber aerogel of the present invention is 690-740 m 2 / g, pore volume is 0.5-0.7cm 3 / g, and the average pore size is 0.4-0.7nm.

[0028] The UiO-66-NH2-F4@ANF fiber aerogel of the present invention has a high specific surface area, a porous structure, and a high porosity, and can provide more active sites and transfer channels for CO2, thereby improving its adsorption capacity for CO2.

[0029] The UiO-66-NH2-F4@ANF fiber aerogel of the present invention has excellent compressive elasticity, with a maximum compressive stress of 15.47 kPa. After 800 compression cycle tests, the plastic deformation is only 7.26%, the maximum compressive stress loss is 4.72%, the Young's modulus loss is only 5.25%, and the energy loss factor loss is only 24.39%.

[0030] The preparation method of the UiO-66-NH2-F4@ANF fiber aerogel of the present invention comprises the following steps: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Cut the aramid fibrils into pieces, add them into an alkaline solution, and reflux them in a constant temperature water bath at 70-90°C for 3-5 hours. After the solution is cooled, filter and wash the solution with distilled water until it is neutral to obtain an aramid fibril solution; The aramid fibrils selected in the present invention may be para-aramid PPTA fibers. The para-aramid PPTA fibers have an obvious skin-core structure and can be easily cracked into nanofibers.

[0031] The aramid fibrils may also be other aramid fibers commonly used in the technical field, and are not specifically limited here.

[0032] The alkaline solution selected in the present invention can be a sodium hydroxide solution, which is not specifically limited herein.

[0033] The purpose of the present invention to perform alkali treatment on aramid fibrils is that aramid fibers have a distinct skin-core structure, that is, the fiber core layer has a higher molecular chain orientation and a higher crystallinity, while the fiber cortex has a lower crystallinity. After alkali treatment, the amide bonds on the surface of the aramid fibers will be hydrolyzed, so that the surface of the aramid fibers acquires electronegativity, that is, the charges on the surface of the aramid fibers repel each other, which is beneficial to the fiber splitting; at the same time, the alkali solution can damage the cortex of the aramid fibers to a certain extent. In other words, after being treated with an alkali solution, the aramid fibrils are more easily cracked, which is more conducive to the transformation into nanofibers. In the subsequent high-pressure homogenization process, the cortex of the aramid fibers will be further destroyed and cracked, which will make it easier to crack into nanofibers.

[0034] If the concentration of the alkali solution is too high, the high-concentration alkali solution will cause serious corrosion damage to the aramid fibrils; if the concentration of the alkali solution is too low, the low-concentration alkali solution cannot make the aramid fiber surface obtain effective electronegativity. After the subsequent high-pressure homogenization treatment, the aramid fiber cannot be effectively cracked into nanofibers, and the diameter distribution of the obtained aramid fiber is uneven, and the aramid fiber has an irregular shape.

[0035] The concentration of the alkaline solution selected in the present invention is 10-20wt%. Within this concentration range, the aramid fibrils will not be corroded and damaged, and the surface of the aramid fibers can obtain effective electronegativity. After subsequent high-pressure homogenization treatment, the aramid fibers can be effectively cracked into nanofibers. The obtained aramid fibers have uniform diameter distribution and regular morphology.

[0036] Preferably, the concentration of the alkaline solution selected in the present invention is 15wt%, the aramid fibrils will not be corroded and damaged, and the aramid fiber surface can obtain effective electronegativity. After subsequent high-pressure homogenization treatment, the aramid fibers can be effectively cracked into nanofibers, and the obtained aramid fibers have uniform diameter distribution and regular morphology.

[0037] The ratio of the mass of the aramid fibrils to the volume of the alkaline solution is (1-3) g: (300-800) ml, and preferably, the ratio of the mass of the aramid fibrils to the volume of the alkaline solution is 2 g: 500 ml; the amide bonds on the surface of the aramid fibers can be fully hydrolyzed without causing corrosion damage to the aramid fibrils, thereby ensuring that the surface of the aramid fibers obtains effective electronegativity, making it easier for the aramid fibers to be cleaved during the subsequent high-pressure homogenization process, thereby obtaining aramid fibers with uniform diameter distribution and regular fiber morphology.

[0038] (1.2) High-pressure homogenization treatment: The aramid fibril solution is treated with a high-pressure homogenizer to obtain an aramid nanofiber solution; the aramid nanofiber solution is filtered and water is removed to obtain aramid nanofibers; The process of treating the aramid fiber solution using a high-pressure homogenizer includes: first using a ball valve to gradually increase the pressure to 700-900 MPa for 15-25 min; then using a flat valve to gradually increase the pressure to 900-1100 MPa for 20-40 min.

[0039] The ball valve can be used to perform rough processing on the aramid fibrils, cut the aramid fibrils, and reduce the diameter and length of the aramid fibrils.

[0040] The flat valve can be used to perform fine processing on the aramid fibrils, shear the aramid fibrils, and further reduce the diameter and length of the aramid fibrils.

[0041] The fiber diameter after flat valve treatment is smaller than that after ball valve treatment, and the fiber diameter distribution will be more uniform, which is conducive to obtaining aramid nanofibers.

[0042] The invention processes aramid fibrils by a high-pressure homogenization method, so that the aramid fibrils are cracked into nanofibers, which is conducive to realizing the mass production of aramid nanofibers, does not require the use of organic solvents, and is safe, environmentally friendly and pollution-free.

[0043] The concentration of the aramid nanofiber solution is 0.3-0.6wt%, preferably, the concentration of the aramid nanofiber solution is 0.4wt%, which can help to filter out the water from the solution, thereby facilitating the acquisition of pure aramid nanofibers.

[0044] (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: the aramid nanofibers were added into the PA solution and stirred for 2 h in a 40° C. water bath; then the ANF was washed with distilled water until neutral and prepared into an ANF aqueous dispersion.

[0045] After phosphoric acid treatment, an affinity substitution reaction and / or hydrolysis reaction can occur between phosphoric acid and aramid nanofibers ANF, which can expose a large number of active groups (amino and carboxyl groups) on the surface of ANF. The active groups (amino and carboxyl groups) on the surface of ANF can react with the metal Zr in the subsequent step (3.2). 4+ A strong interfacial hydrogen bond is formed between them, and finally the UiO-66-NH2-F4 particles are uniformly and heavily loaded on the ANF surface.

[0046] The concentration of the PA solution is 15-25wt%, preferably, the concentration of the PA solution is 20wt%, which can cause a large number of active groups (amino and carboxyl groups) to be fully exposed on the surface of the ANF, which is beneficial for the uniform and large-scale loading of UiO-66-NH2-F4 particles on the surface of the ANF, and will not cause corrosion damage to the ANF fibers.

[0047] The ratio of the mass of aramid nanofibers to the volume of PA solution is (0.5-1.5) g: (200-400) ml; this can promote the full hydrolysis of ANF, so that a large number of active groups (amino and carboxyl groups) are fully exposed on the surface of ANF, which is beneficial to the uniform and large-scale loading of UiO-66-NH2-F4 particles on the surface of ANF without causing corrosion damage to the ANF fibers.

[0048] The concentration of ANF aqueous dispersion is 0.2-0.5wt%, preferably, the concentration of ANF aqueous dispersion is 0.3-0.4wt%, which is beneficial to improve the specific surface area, porosity and mechanical properties of fiber aerogel. Specifically, the fiber aerogel prepared by freeze-drying and heat curing treatment of ANF dispersion of this concentration can have the characteristics of light weight and excellent mechanical properties. If the concentration is further increased, the density of fiber aerogel prepared by the same volume of aqueous dispersion will be large, and the structure will be denser, resulting in a decrease in the porosity and specific surface area of ​​the fiber aerogel; at the same time, a high MOF content will cause the aerogel to become more brittle, which will eventually lead to a decrease in the mechanical properties of the fiber aerogel.

[0049] (3) Preparation of UiO-66-NH2-F4 fiber aerogel (3.1) Place the ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare an ANF / DMF dispersion; The concentration of ANF / DMF dispersion is 0.2-0.5wt%, preferably, the concentration of ANF / DMF dispersion is 0.3-0.4wt%, which is beneficial to improve the specific surface area, porosity and mechanical properties of fiber aerogel. Specifically, the fiber aerogel prepared by freeze-drying and heat curing treatment of ANF dispersion of this concentration can have the characteristics of light weight and excellent mechanical properties. If the concentration of ANF / DMF dispersion is too high, the density of fiber aerogel prepared by the same volume of water dispersion will be large, and the structure will be denser, resulting in a decrease in the porosity and specific surface area of ​​the fiber aerogel; at the same time, if the concentration of ANF / DMF dispersion is too high, the MOF content is high, which will cause the aerogel to become more brittle, and ultimately lead to a decrease in the mechanical properties of the fiber aerogel.

[0050] A high MOF content will increase the brittleness of the aerogel, which will eventually lead to a decrease in the mechanical properties of the fiber aerogel.

[0051] (3.2) Weigh zirconium salt ZrCl4 and add it to the ANF / DMF dispersion, stirring until it is completely dissolved; then add H2BDC-NH2, H2BDC-F4 and glacial acetic acid HOAc, continue stirring to obtain a mixed solution; The role of adding zirconium salt first: After the ANF fiber is treated with PA, a large number of carboxyl functional groups will be generated on the surface of the ANF fiber, and the metal Zr 4+ It will produce metal complexation with carboxyl groups, thereby inducing metal Zr 4+ With the addition of ligands H2BDC-NH2 and H2BDC-F4, H2BDC-NH2 and H2BDC-F4 will spontaneously bind to the metal Zr loaded on the ANF surface. 4+ Combined with each other, UiO-66-NH2-F4 was in situ assembled on the ANF surface, which was beneficial to the uniform and large-scale loading of UiO-66-NH2-F4 on the ANF surface.

[0052] 2-Aminoterephthalic acid H2BDC-NH2 contains polar functional groups amino and carboxyl, which can make the microporous environment of the fiber aerogel have a strong affinity for CO2 molecules.

[0053] 2,3,5,6-tetrafluoroterephthalic acid H2BDC-F4 contains non-polar functional groups such as fluorine, which can be modified by fluorination, greatly improving the wet stability of the chemical microenvironment of the fiber aerogel, making the fiber aerogel change from hydrophilic to hydrophobic, and constructing a microporous environment that is pro-CO2 molecules and repellent to H2O molecules.

[0054] The role of glacial acetic acid is to promote better crystallization of UiO-66-NH2-F4, which is beneficial to present a better UiO-66-NH2-F4 crystal structure.

[0055] The mass ratio of glacial acetic acid to zirconium salt is (0.8-1.2):(3-6). Preferably, the mass ratio of glacial acetic acid to zirconium salt is 1:5, which can promote better crystallization of UiO-66-NH2-F4 and help it present a good crystal structure and crystal morphology.

[0056] (3.3) transferring the mixed solution to a reactor for reaction, and after the reaction is completed and cooled to room temperature, obtaining UiO-66-NH2-F4@ANF fibers by suction filtration; In the reactor, the reaction temperature is 110-130°C and the reaction time is 10-14h.

[0057] (3.4) Wash the UiO-66-NH2-F4@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-66-NH2-F4@ANF fiber dispersion; The concentration of the UiO-66-NH2-F4@ANF fiber dispersion is 0.2-0.5wt%, preferably, the concentration of the UiO-66-NH2-F4@ANF fiber dispersion is 0.3-0.4wt%, which is beneficial to improve the specific surface area, porosity and mechanical properties of the fiber aerogel. Specifically, the fiber aerogel prepared by the ANF dispersion of this concentration after subsequent freeze drying and heat curing treatment can have the characteristics of light weight and excellent mechanical properties. If the concentration of the UiO-66-NH2-F4@ANF fiber dispersion is too high, the density of the fiber aerogel prepared by the same volume of water dispersion will be large, and the structure will be more compact, resulting in a decrease in the porosity and specific surface area of ​​the fiber aerogel; at the same time, if the concentration of the UiO-66-NH2-F4@ANF fiber dispersion is too high, the MOF content is high, which will cause the aerogel to become more brittle, and ultimately lead to a decrease in the mechanical properties of the fiber aerogel.

[0058] (3.5) Take the UiO-66-NH2-F4@ANF fiber dispersion, add aqueous silane solution and tert-butyl alcohol, stir, and obtain UiO-66-NH2-F4@ANF fiber aerogel through freeze drying and thermal curing.

[0059] The volume of UiO-66-NH2-F4@ANF fiber dispersion, the mass of aqueous silane solution and the volume ratio of tert-butanol are (8-12) mL: (0.01-0.05) g: (0.5-1.5) ml; on the one hand, tert-butanol can maximize the promotion of UiO-66-NH2-F4@ANF fiber dispersion to form a well-formed ice crystal structure and ice crystal morphology during the freezing process; on the other hand, it can ensure that the aqueous silane can be completely thermally cured, so that it can effectively promote the bonding between fibers and ensure that the UiO-66-NH2-F4@ANF fiber aerogel obtains excellent compression-rebound properties.

[0060] The freeze drying temperature is -60-40℃ and the time is 30-40 hours. The heat curing temperature is 160-200℃ and the time is 3-8 minutes.

[0061] The role of tert-butanol: By adding tert-butanol to the UiO-66-NH2-F4@ANF fiber dispersion, it is beneficial to promote the UiO-66-NH2-F4@ANF fiber dispersion to form a good ice crystal structure and ice crystal morphology during the freezing process; after the drying process, the ice crystals will sublimate, and the pores of the UiO-66-NH2-F4@ANF fiber aerogel will be formed where the ice crystals exist, and finally the block-shaped three-dimensional structure of the UiO-66-NH2-F4@ANF fiber aerogel is obtained, so that the aerogel has a three-dimensional multi-level pore structure, giving it excellent mechanical properties, such as compression-rebound properties. If tert-butanol is not added and the aqueous dispersion of the UiO-66-NH2-F4@ANF fiber is directly frozen, the size of the ice crystals will be abnormally disordered, resulting in the final UiO-66-NH2-F4@ANF fiber aerogel The pores are also very disordered and cannot give it excellent mechanical properties.

[0062] Purpose of freeze-drying: By freezing the aqueous dispersion of UiO-66-NH2-F4@ANF fibers, a solid material with a three-dimensional block structure (with ice crystals) can be obtained, which is conducive to the formation of a well-shaped ice crystal structure in the freezing process of the UiO-66-NH2-F4@ANF fiber dispersion; and then through the drying process, the ice crystals will sublime, and the pores of the UiO-66-NH2-F4@ANF fiber aerogel will be formed where the ice crystals exist, so that the aerogel forms a three-dimensional porous structure, giving the aerogel excellent mechanical properties, such as compression-rebound properties.

[0063] The role of water-based silane: By subjecting the freeze-dried UiO-66-NH2-F4@ANF fiber aerogel to high-temperature heat treatment, the silane in it will be thermally cured, thereby promoting adhesion between fibers, and ultimately giving the UiO-66-NH2-F4@ANF fiber aerogel excellent mechanical properties, such as compression-rebound properties. If silane is not added, the UiO-66-NH2-F4@ANF fiber aerogel will not have elasticity after compression.

[0064] Purpose of thermal curing: By subjecting the freeze-dried UiO-66-NH2-F4@ANF fiber aerogel to high-temperature heat treatment, the silane therein will be thermally cured, thereby promoting bonding between the fibers, and ultimately giving the UiO-66-NH2-F4@ANF fiber aerogel excellent mechanical properties (compression-rebound properties).

[0065] The beneficial technical effects of this application include: (1) Compared with the traditional method of using potassium hydroxide (KOH) and 2-methyl sulfoxide (DMSO) to first deprotonate the aramid primary fiber and then use water as a proton donor to reduce it to obtain ANF, the present application adopts a high-pressure homogenization process to convert micron-sized aramid fibers into aramid nanofibers ANF, which can realize the batch preparation of ANF without the use of organic solvents. The ANF production efficiency is high and it is safe, environmentally friendly and pollution-free.

[0066] (2) Phosphoric acid treatment of ANF can expose a large number of active groups (amino and carboxyl groups) on the surface of ANF, thereby allowing the carboxyl groups to react with metal Zr 4+ A strong interfacial hydrogen bond is formed between them, and finally UiO-66-NH2-F4 is uniformly and heavily loaded on the ANF surface, which can better promote the in situ growth of UiO-66-NH2-F4 on the ANF surface.

[0067] (3) Through the fiber freeze-drying technology, by freezing the aqueous dispersion of UiO-66-NH2-F4@ANF fibers, a block-shaped three-dimensional solid material (with ice crystals) can be obtained, which is conducive to the formation of a well-shaped ice crystal structure in the freezing process of the UiO-66-NH2-F4@ANF fiber dispersion; then after the drying process, the ice crystals will sublimate, and the pores of the UiO-66-NH2-F4@ANF fiber aerogel will be formed where the ice crystals exist, so that the aerogel forms a three-dimensional porous structure, giving the aerogel excellent mechanical properties, such as compression-rebound properties; after 800 compression-rebound test tests, the UiO-66-NH2-F4@ANF fiber aerogel can still maintain a complete aerogel morphology.

[0068] (4) The UiO-66-NH2-F4 fiber aerogel of the present invention has a three-dimensional multi-level pore structure integrating macropores, mesopores and micropores, wherein the macropores and mesopores formed by the three-dimensional interconnected fiber network can be used as continuous long-range gas transmission channels, effectively improving the efficient diffusion of gas molecules inside it; and the UiO-66-NH2-F4 distributed in the three-dimensional nanofiber network channel retains an open microporous structure, which can provide more contact area, active sites and transmission channels for CO2, thereby improving its adsorption capacity for CO2; at the same time, the hydrophobic micropores can also limit H2O molecules and promote the adsorption of CO2 molecules into the interior of the UiO-66-NH2-F4 fiber aerogel.

[0069] (5) The MOF precursor of the present application includes zirconium chloride (ZrCl4) and two organic ligands, 2-aminoterephthalic acid (H2BDC-NH2) and 2,3,5,6-tetrafluoroterephthalic acid (H2BDC-F4). 2-aminoterephthalic acid H2BDC-NH2 contains polar functional groups, amino and carboxyl, which can make the microporous environment of the fiber aerogel have a strong affinity for CO2 molecules. 2,3,5,6-tetrafluoroterephthalic acid H2BDC-F4 contains non-polar functional groups such as fluorine, and can be fluorinated to greatly improve the wet stability of the chemical microenvironment of the fiber aerogel, so that the fiber aerogel changes from hydrophilic to hydrophobic, and constructs a microporous environment that is pro-CO2 molecules and repellent to H2O molecules.

[0070] Therefore, the UiO-66-NH2-F4 fiber aerogel of the present application has a strong affinity for CO2 molecules, which can improve the CO2 adsorption efficiency and adsorption performance. The UiO-66-NH2-F4@ANF fiber aerogel of the present invention can be used to prepare carbon dioxide separation and / or adsorption materials. Example

[0071] The preparation method of the UiO-66-NH2-F4@ANF fiber aerogel of this embodiment includes the following steps: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Weigh 2 g of aramid fibrils and cut them into pieces, add them into 500 mL of 15 wt% sodium hydroxide solution, reflux in a constant temperature water bath at 80 °C for 4 h, and after the solution is cooled, filter and wash with distilled water until it is neutral to obtain an aramid fibril solution; (1.2) High-pressure homogenization treatment: The aramid fibril solution is treated by a high-pressure homogenizer to obtain an aramid nanofiber solution with a concentration of 0.4 wt %; the aramid nanofiber solution is filtered and water is removed to obtain aramid nanofibers; The process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to gradually increase the pressure to 800 MPa for 20 minutes; then using a flat valve to gradually increase the pressure to 1000 MPa for 30 minutes.

[0072] (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: 0.1 g ANF was added to 30 mL of 20 wt% PA solution and stirred in a 40 ℃ water bath for 2 h; then the ANF was washed with distilled water until neutral and prepared into an ANF aqueous dispersion with a mass fraction of 0.3 wt%.

[0073] (3) Preparation of UiO-66-NH2-F4@ANF fiber aerogel (3.1) Place 30 mL of 0.3 wt% ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare a 0.3 wt% ANF / DMF dispersion; (3.2) Weigh 0.09 g of zirconium salt ZrCl4 into the ANF / DMF dispersion and stir for 15 min until it is completely dissolved; then add 0.108 g of H2BDC-NH2, 0.108 g of H2BDC-F4 and 0.108 g of glacial acetic acid HOAc and continue stirring for 15 min to obtain a mixed solution; (3.3) The mixed solution was transferred to a reactor and reacted at 120° C. for 12 h. After the reaction was completed and cooled to room temperature, UiO-66-NH2-F4@ANF fibers were obtained by suction filtration. (3.4) Wash the UiO-66-NH2-F4@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-66-NH2-F4@ANF fiber into a UiO-66-NH2-F4@ANF fiber dispersion with a concentration of 0.3wt%; (3.5) Take 10 ml of the above UiO-66-NH2-F4@ANF fiber dispersion, add 0.03 g of aqueous silane solution and 1 mL of tert-butyl alcohol, stir for 15 min, and freeze-dry and heat-cure to obtain UiO-66-NH2-F4@ANF fiber aerogel. The freeze-drying temperature is -50 °C and the time is 36 h; the heat-cure temperature is 180 °C and the time is 5 min.

[0074] The SEM test results of the UiO-66-NH2-F4@ANF fiber aerogel in Example 1 are as follows: Figure 1 As shown. Figure 1It can be seen that after UiO-66-NH2-F4 was in situ assembled on the ANF surface, evenly distributed particles appeared on the surface of the UiO-66-NH2-F4@ANF fiber aerogel, and the particles were UiO-66-NH2-F4 (ie, MOF).

[0075] The UiO-66-NH2-F4@ANF fiber aerogel of Example 1 was subjected to 800 cycles of compression-rebound test under the test condition of 50% deformation. The measured stress-strain curve is shown in the figure below: Figure 2 As shown. Figure 2 It can be explained that the UiO-66-NH2-F4@ANF fiber aerogel of this embodiment can still maintain a complete aerogel morphology structure after 800 cycles of compression-rebound test, indicating that the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 has excellent compression rebound performance.

[0076] The MOF loading amount of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 was calculated. By weighing on a balance, it was calculated that the MOF loading amount on the surface of the UiO-66-NH2-F4@ANF fiber aerogel was 79.26%.

[0077] The pore size distribution of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 was tested. Figure 3 (a) The pore size distribution curve calculated by mercury intrusion method shows that the macropore diameter of UiO-66-NH2-F4@ANF fiber aerogel is distributed between 1-100 μm; Figure 3 (b) The pore size distribution curve calculated by the BJH model shows that the pore sizes of the micropores and mesopores of UiO-66-NH2-F4@ANF fiber aerogel are concentrated between 0.18 and 2 nm. This shows that UiO-66-NH2-F4@ANF fiber aerogel has an obvious three-dimensional multi-level pore structure, in which the macropores and mesopores are conducive to promoting the transmission and diffusion of CO2 gas molecules, while the micropores can effectively improve the adsorption of CO2 gas molecules by UiO-66-NH2-F4@ANF fiber aerogel.

[0078] The specific surface area, pore volume and average pore size can be obtained by using a fully automatic specific surface area and porosity analyzer. The specific surface area of ​​the UiO-66-NH2-F4@ANF fiber aerogel in Example 1 is 728.52 m 2 / g, pore volume 0.628cm 3 / g, and the average pore size is 0.519nm. The UiO-66-NH2-F4@ANF fiber aerogel of Example 1 has a high specific surface area, a porous structure, and a high porosity, which can provide more active sites and transfer channels for CO2, thereby improving its adsorption capacity for CO2.

[0079] Comparative Example 1 The preparation method of the ANF fiber aerogel of this comparative example includes the following preparation process: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Weigh 2 g of aramid fibrils and cut them into pieces. Add them into 500 mL of 15 wt.% sodium hydroxide (NaOH) alkaline solution and reflux them in a constant temperature water bath at 80 °C for 4 h. After the solution is cooled, filter it with distilled water and wash it until it is neutral to obtain an aramid fibril solution. (1.2) High-pressure homogenization treatment: The aramid fibril solution is treated by a high-pressure homogenizer to obtain an aramid nanofiber solution with a concentration of 0.4 wt %; the aramid nanofiber solution is filtered and water is removed to obtain aramid nanofibers; The process of treating the aramid fibril solution with a high-pressure homogenizer includes: first using a ball valve to gradually increase the pressure to 800 MPa for 20 minutes; then using a flat valve to gradually increase the pressure to 1000 MPa for 30 minutes.

[0080] (2) Preparation of ANF fiber aerogel Take 10 ml of the above ANF fiber dispersion, add 0.03 g of aqueous silane solution and 1 mL of tert-butyl alcohol, stir for 15 min, and then freeze-dry and heat-cure to obtain ANF fiber aerogel. The freeze-drying temperature is -50 ° C, the time is 36 h; the heat-cure temperature is 180 ° C, and the time is 5 min.

[0081] Figure 4 This is the SEM image of the ANF fiber aerogel prepared in this comparative example 1. Figure 4 It can be shown that the surface of the ANF fiber aerogel in Comparative Example 1 is flat and smooth, without loading other substances, and the diameter of the ANF fiber is concentrated in the range of 20-200 nm.

[0082] The CO2 adsorption capacity of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 and the ANF fiber aerogel of Comparative Example 1 at 25°C was tested. Figure 5 As shown. Figure 5 It can be seen that the adsorption capacity of CO2 of UiO-66-NH2-F4@ANF fiber aerogel in Example 1 is much greater than the adsorption capacity of CO2 of ANF fiber aerogel in Comparative Example 1.

[0083] The adsorption capacity of H2O (gaseous) at 25°C for the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 and the ANF fiber aerogel of Comparative Example 1 was tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the adsorption capacity of UiO-66-NH2-F4@ANF fiber aerogel in Example 1 for H2O (gaseous state) is much smaller than that of ANF fiber aerogel in Comparative Example 1 for H2O (gaseous state). This is because the surface of UiO-66-NH2-F4@ANF fiber aerogel in Example 1 contains fluorine functional groups, and the use of ligands containing non-polar functional groups such as fluorine for fluorination modification design can greatly improve the wet stability of the MOF chemical microenvironment, so that MOF changes from hydrophilic to hydrophobic, and constructs a microporous environment that is hydrophilic to CO2 molecules and hydrophobic to H2O molecules.

[0084] The XRD test results of the UiO-66-NH2-F4@ANF fiber aerogel of Example 1 and the ANF fiber aerogel and UiO-66-NH2-F4 crystal of Comparative Example 1 are as follows: Figure 7 As shown. Figure 7 It can be seen that the particles on the fiber surface of UiO-66-NH2-F4@ANF fiber aerogel are UiO-66-NH2-F4, indicating that UiO-66-NH2-F4 is loaded on the ANF surface.

[0085] The above embodiments are only used to illustrate the equivalent replacement of the technical lines of the present invention; these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions claimed to be protected by the present invention, nor do they limit them; although the present invention has been described in detail with reference to the above embodiments, it is still possible for ordinary technicians in this field to modify the technical solutions recorded in the above embodiments, or to improve the spirit and scope of some of the technical features therein.

Claims

1. A UiO-66-NH2-F4@ANF fiber aerogel, characterized in that: include: MOF precursor and aramid nanofiber ANF, wherein the MOF precursor comprises zirconium salt, 2-aminoterephthalic acid H2BDC-NH2 and 2,3,5,6-tetrafluoroterephthalic acid H2BDC-F4; The mass ratio of zirconium salt, H2BDC-NH2, H2BDC-F4 and ANF is (0.8-1.2): (1-1.5): (1-1.5): (0.8-1.2); The specific surface area of ​​the UiO-66-NH2-F4@ANF fiber aerogel is 600-750 m 2 / g, pore volume is 0.5-0.8cm 3 / g, and the average pore size is 0.3-1nm.

2. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 1, characterized in that: include: (1) Preparation of aramid nanofibers (1.1) Alkali treatment: Cut the aramid fibrils into pieces, add them into an alkaline solution, reflux them in a constant temperature water bath, and after the solution is cooled, filter and wash the solution with distilled water until it is neutral to obtain an aramid fibril solution; (1.2) High-pressure homogenization treatment: using a high-pressure homogenizer to treat the aramid fibril solution to obtain an aramid nanofiber solution; filtering the aramid nanofiber solution to remove water to obtain aramid nanofibers; (2) Preparation of ANF aqueous dispersion Phosphoric acid PA treatment: adding the aramid nanofibers to the PA solution and stirring under water bath conditions; then washing the ANF with distilled water until it is neutral and preparing an ANF aqueous dispersion; (3) Preparation of UiO-66-NH2-F4@ANF fiber aerogel (3.1) Place the ANF aqueous dispersion in N, N-dimethylformamide (DMF) to prepare an ANF / DMF dispersion; (3.2) Weighing a zirconium salt, adding it to the ANF / DMF dispersion, and stirring until it is completely dissolved; then adding H2BDC-NH2, H2BDC-F4 and glacial acetic acid HOAc, and continuing to stir to obtain a mixed solution; (3.3) transferring the mixed solution to a reactor for reaction, and after the reaction is completed and cooled to room temperature, obtaining UiO-66-NH2-F4@ANF fibers by suction filtration; (3.4) Wash the UiO-66-NH2-F4@ANF fiber three times with DMF and methanol respectively to remove unreacted impurities; then replace the solvent with distilled water to prepare the UiO-66-NH2-F4@ANF fiber dispersion; (3.5) Take the UiO-66-NH2-F4@ANF fiber dispersion, add aqueous silane solution and tert-butyl alcohol, stir, and obtain UiO-66-NH2-F4@ANF fiber aerogel through freeze drying and thermal curing.

3. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In the step (1.1), the alkaline solution is a sodium hydroxide solution with a concentration of 10-20 wt%; The ratio of the mass of the aramid fiber to the volume of the alkaline solution is (1-3) g: (300-800) ml; Reflux in a constant temperature water bath at 70-90℃ for 3-5h.

4. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In the step (1.2), the concentration of the aramid nanofiber solution is 0.3-0.6 wt %; The process of treating the aramid fiber solution with a high-pressure homogenizer includes: first using a ball valve to increase the pressure to 700-900 MPa for 15-25 minutes; Then use a flat valve to increase the pressure to 900-1100 MPa and treat for 20-40 minutes.

5. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In step (2), the concentration of the PA solution is 15-25wt%; The ratio of the mass of the aramid nanofiber to the volume of the PA solution is (0.5-1.5) g: (200-400) ml; Stir in a 40 °C water bath for 2 h; The concentration of the ANF aqueous dispersion is 0.2-0.5 wt %.

6. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.1), the concentration of the ANF / DMF dispersion is 0.2-0.5wt%.

7. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.2), the mass ratio of the glacial acetic acid to the zirconium salt is (0.8-1.2):(3-6).

8. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.3), the reaction temperature in the reactor is 110-130°C and the reaction time is 10-14h; In the step (3.4), the concentration of the UiO-66-NH2-F4@ANF fiber dispersion is 0.2-0.5wt%.

9. The method for preparing the UiO-66-NH2-F4@ANF fiber aerogel according to claim 2, characterized in that: In the step (3.5), the volume ratio of the UiO-66-NH2-F4@ANF fiber dispersion, the mass of the aqueous silane solution and the volume ratio of the tert-butyl alcohol is (8-12) mL: (0.01-0.05) g: (0.5-1.5) ml; The freeze-drying temperature is -60--40℃ and the time is 30-40 h; The thermal curing temperature is 160-200°C and the time is 3-8 minutes.

10. Use of the UiO-66-NH2F4@ANF fiber aerogel according to claim 1 in preparing carbon dioxide separation and / or adsorption materials.

Citation Information

Patent Citations

  • Preparation method of elastic super-hydrophobic oleophylic MOF / SiO2 composite aerogel

    CN115845813A

  • UiO-66-NH2-coated ANFs aerogel as well as preparation method and application thereof

    CN116656135A

  • MOF-containing aramid fiber aerogel as well as preparation method and application thereof

    CN118772647A

Cited By

  • Preparation method of aluminum-based MOF nanofiber aerogel

    CN122006606A

  • Preparation method of aluminum-based MOF nanofiber aerogel

    CN122006606B